Manifestations of symbolism and its forms in the poetry of Abu Al-Tayeb Al-Randi (d. 684 AH) - Yassine , Sameer (Al-Adab Journal, 2024)
This research came under the title (Manifestations of symbols in the poetry of Abi Al-Tayib Al-Rendi, 684 {migration}). It represented a preliminary and two bases; the preliminary covered the definition of a symbol and a synopsis of the poet’s life. What covered the first base was the manifestations of neutral symbols, which constituted symbolics of: night, day, seas, plants, and animals, and revealed their symbolics in his poetry and poems for all different needs. Furthermore, the second base followed studying the manifestation of colour symbolics, and the poet’s composition of the colour symbols in his poetic poems, which followed the delivery of these symbols to satisfy, pander, and pleasure the reader, or would it fail to represent the meaning that it was meant to be? Moreover, here comes the researcher’s answer to explain the symbolics and reveal their effects on what the poet meant.